Synthesis and characterisation of biomaterials for use as markers of health and disease : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Chemistry at Massey University - Desai, Rakesh Natverlal (Massey University, 2001)
The bicyclic[4.3.0]nonane ring system is commonly found in many complex bioactive natural products, such as spongians and several novel steroids. Previous examples of ester tethered cycloaddition reactions were limited to activated dienes and dienophiles. The synthesis of a range of precursors, in which an unactivated diene and dienophile were linked via an ester tether is described. Model studies into the synthesis of monocyclic and bicyclic lactones as possible pre requisites for the formation of the C/D rings of the spongian skeleton utilising intramolecular Diels-Alder reaction (IMDA) or alternative cyclisation methods such as free radical catalysed and Heck reaction were carried out with these substrates. However it was discovered that when the carbonyl group of the ester tether was in conjugation with the diene it caused a formidable challenge as none of the applied methods were found to be suitable for the cyclisation reactions. Chapters two to five were focused on attempts to synthesise glucuronides of phytoestrogen metabolites (isoflavones and isoflavans) glucuronide due to their potential interest as anti cancer agents. Also the steroidal hormone estrone glucuronide (for fertility testing) and testosterone glucuronide (for use in clinical laboratories and for drug testing) for the purpose of developing multipurpose home monitor by adapting the platform technology previously developed and used in a point-of-care monitoring device known as the Ovarian Monitor. The synthesis of phytoestrogen glucuronide is a relatively new concept and the literature revealed no successful chemical method to date. The desired phytoestrogen isoflavones required for stereoselective glucuronidation were successfully prepared from precursor deoxybenzoins using a new convenient and facile route. Reduction of the isoflavones to isoflavans was also carried out using standard literature procedures. Various activated and deactivated phenols (including a sterically hindered phenol) were successfully glucuronidated using various synthetic routes as model studies. The information garnered from the model studies was utilised for the glycosylation of isoflavones and isoflavan but numerous attempts to obtained the glucuronides by using direct methods failed. Even more reactive glycosyl donors such as the sulfoxide sugar and acetimidate sugar also failed to effect glycosylation of these phytoestrogen metabolites. The relative insolubility and instability of the chromene ring under acid-base reaction conditions were compounding problems for the isoflavones. A new alternative route involving synthesis of the O-glucuronides by the prior synthesis of the glycosides, hydrolysis to the glucosides and then TEMPO mediated selective oxidation of the primary alcohol was successful for simple phenol, sterically hindered phenol and the steroids estrone and testosterone. However, this alternative route also failed to effect glucuronidation of the isoflavones. Attention was thus focused on the synthesis of isoflavone glucuronides using UDP-glucuronyl transferase. Towards this end (±) methoxy equol glucuronide has been synthesised enzymatically, and purified using chromatographic methods. The attempted enzymatic synthesis of formononetin gave instead the cleavage product 2-hydroxy, 4'-methoxy deoxybenzoin glucuronide. The glucuronides were fully characterised by 1H-1H 2D-COSY, 1H-13C 2D-HETCOR and DEPT spectra and the results unambiguously showed the β-linkage of the glucuronide ring with the aglycon moieties. The presence of the glucuronide ring at the C-4 position in 2-hydroxy, 4'-methoxy deoxybenzoin glucuronide was also confirmed by a long range coupling experiment(HMBC). The stereochemical integrity of the estrone glucuronide (E1G) obtained using perester coupling, acetimidate coupling and TEMPO catalysed oxidation methods were clinically tested by comparison with a standard curve obtained with a sample produced by the Koenigs-Knorr method. Testosterone glucuronide was studied for use as a biomarker to validate the concept of a multi-purpose home monitor for a variety of analyte glucuronides of clinical interest. Testosterone glucuronide antibodies with high affinity were generated by immunisation of sheep and testosterone glucuronide-HEW lysozymes conjugates were prepared. The standard curve for TG clearly showed it can be used for measurement of urinary TG at physiological concentrations. This methodology can be extended for analyte glucuronides of interest and can be used for development of biomarkers for health and disease. Thus a multi-purpose home monitor is now a reality and exciting commercial and practical applications are expected in the future.
Keywords: Glucuronides; Organic compounds; Chemical compounds; Home monitor; Fields of Research::250000 Chemical Sciences::250300 Organic Chemistry::250301 Organic chemical synthesis